2022
DOI: 10.3390/s22207968
|View full text |Cite
|
Sign up to set email alerts
|

Local Path Planning of Autonomous Vehicle Based on an Improved Heuristic Bi-RRT Algorithm in Dynamic Obstacle Avoidance Environment

Abstract: The existing variants of the rapidly exploring random tree (RRT) cannot be effectively applied in local path planning of the autonomous vehicle and solve the coherence problem of paths between the front and back frames. Thus, an improved heuristic Bi-RRT algorithm is proposed, which is suitable for obstacle avoidance of the vehicle in an unknown dynamic environment. The vehicle constraint considering the driver’s driving habit and the obstacle-free direct connection mode of two random trees are introduced. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Therefore, we propose a tree expansion method with a dynamic step size. The dynamic step method proposed in the current literature (Wang et al, 2022a;Zhang et al, 2022a;Yang et al, 2021) only dynamically changes the step size in the expansion of the tree depending on whether the current node collides with an obstacle or not. If no collision occurs, the step size is expanded, and if a collision occurs, the new node is re-found and expanded with a small step size.…”
Section: Dynamic Variable Step Samplingmentioning
confidence: 99%
“…Therefore, we propose a tree expansion method with a dynamic step size. The dynamic step method proposed in the current literature (Wang et al, 2022a;Zhang et al, 2022a;Yang et al, 2021) only dynamically changes the step size in the expansion of the tree depending on whether the current node collides with an obstacle or not. If no collision occurs, the step size is expanded, and if a collision occurs, the new node is re-found and expanded with a small step size.…”
Section: Dynamic Variable Step Samplingmentioning
confidence: 99%
“…The simulation indicated that the vehicle could successfully track the path efficiently and reach the destination safely. An improved heuristic Bi-RRT algorithm, specialized for an unknown dynamic environment, was put forward by [ 9 ] for obstacle avoidance. Thence, the related experiments have verified the good performance of such an algorithm in differentiable coherence path generation, ensuring both ride comfort and stability of the vehicle.…”
Section: Introduction and Backgroundsmentioning
confidence: 99%
“…This Special Issue on Sensors aims to report on some of the recent research efforts on this increasingly important topic. The 11 accepted papers in this Issue cover vehicle position estimation [ 1 ], 3D Object Detection [ 2 ], pedestrian state sense [ 3 ], trajectory prediction [ 4 ], criticality assessment [ 5 ], active fault-tolerant control for actuator failure [ 6 ], decision-making in the scenario of highway driving out of the ramp [ 7 ] and uncertain interactive traffic scenarios [ 8 ], RRT-based path planning algorithm [ 9 ], C/GMRES motion planning algorithm [ 10 ], and lane-keeping controller design [ 11 ]. In this introduction, a brief description of the content of each contribution forming the Special Issue is provided.…”
mentioning
confidence: 99%
“…Ref. [ 9 ] proposes using an improved heuristic Bi-RRT algorithm to obtain a smooth and asymptotically optimal path, with continuous curvature possessing high efficiency and accuracy in an uncertain dynamic environment. The consideration of the driver’s driving habit and the obstacle-free direct connection mode of two trees, as well as the introduction of the greedy step size and the design of the path reorganization, can expand the node more effectively, make the path smooth, and ensure the ride comfort of the vehicle.…”
mentioning
confidence: 99%
See 1 more Smart Citation